Effect of mung bean sprout (Vigna radiata) germination phases on the physical and sensory quality of nata de coco - ANDRIANSYAH ANDRIANSYAH; AKHMAD FATHIR; LINDA TRI ANTIKA (Smujo International, 2025)
Abstract. Andriansyah, Fathir A, Antika LT. 2025. Effect of mung bean sprout (Vigna radiata) germination phases on the physical and sensory quality of nata de coco. Asian J Agric 9: 787-799. The use of natural nitrogen sources in nata de coco production is essential to enhance food safety and promote sustainable fermentation practices. This study evaluated the effect of mung bean sprout (Vigna radiata) germination phases 24 hours (F1), 48 hours (F2), and 72 hours (F3) as natural nitrogen sources on the physical and sensory properties of nata de coco. Sprout extracts were mixed with coconut water and sugar, inoculated with Acetobacter xylinum at a density of 1×10⁸ CFU/mL, and fermented for 15 days. The observed parameters included thickness, weight, total soluble solids, and sensory attributes (aroma and taste) assessed using a three-point hedonic scale. Statistical analysis revealed no significant differences (p>0.05) among germination phases in all measured parameters, although the 48-hour treatment tended to produce nata with slightly better physical and more balanced sensory characteristics. These findings indicate that within the 24-72-hour window, sprout physiological maturity only modestly affects nitrogen availability, suggesting that the use of sprout extract itself as a natural nitrogen source is more influential than germination duration. Overall, this study reinforces the potential of mung bean sprout extract as a safe, eco-friendly, and sustainable alternative to synthetic nitrogen sources in microbial cellulose production, supporting the development of environmentally responsible food biotechnology.